2021
DOI: 10.3390/jpm11050349
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Secretion and Receptor Expression Determine the Age-Related Degree of Osteogenic Differentiation in Dental Pulp Stem Cells

Abstract: Objective: To demonstrate the levels of parathyroid hormone secretion and genetic expressions of parathyroid hormone (PTH) and PTH1 receptor (PTH1R) genes in the dental pulp stem cells (DPSCs) from different age groups before and after induction of osteogenic differentiation. In addition, we also wanted to check their correlation with the degree of osteogenic differentiation. Methods: Human primary DPSCs from three age groups (milk tooth (SHEDs), 7–12 years old; young DPSCs (yDPSCs), 20–40 years old; old DPSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Lastly, OC is a main non-collagenous component synthesized by osteoblast during bone regeneration [ 52 ]. Moreover, some studies indicated that aging affected the expression of PTH and PTH1R and thwarted their protein translation that had been shown to regulate and augment the osteogenic differentiation of various hDPSCs [ 53 ]. These results showed that CA-modified MTA could enhance in vitro osteogenesis which was hypothesized to be due to increased cellular proliferation and VEGF and Ang-1 expressions as seen above.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, OC is a main non-collagenous component synthesized by osteoblast during bone regeneration [ 52 ]. Moreover, some studies indicated that aging affected the expression of PTH and PTH1R and thwarted their protein translation that had been shown to regulate and augment the osteogenic differentiation of various hDPSCs [ 53 ]. These results showed that CA-modified MTA could enhance in vitro osteogenesis which was hypothesized to be due to increased cellular proliferation and VEGF and Ang-1 expressions as seen above.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Qu et al [ 35 ] and Zhang et al [ 29 ] examined three osteogenic-induced and three non-induced samples, whereas some authors did not mention the number of samples tested, and the period of osteogenic induction varied widely (3, 5, 7, or 14 days) between studies. It has been suggested that aging can affect the characteristics of the regenerative potentials of dental-derived stem cells [ 87 , 88 ]. Moreover, differences in library preparation, sequencing techniques, and methods of analysis may also have led to the variations in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous NO promoted DPSC differentiation into odontoblasts and induced tertiary dentin formation in rats [34]. Therefore, NTAPP's effects on differentiation could be expanded to guide endocrine/paracrine conditioned cells toward various osteogenic/chondrogenic lineages [35,36]. Long term observation using HTM will be required to trace these subcellular changes during differentiation.…”
Section: Discussionmentioning
confidence: 99%